Фільтрація неоднорідності випромінюючої здатності методом зонної та інтегральної фільтрації у тепловому неруйнівному контролі - Сафонов, О. О.; Шокун, А. С. (ХНУРЕ, 2021)
The possibility of thermographic method application to the estimation of gas-main pipeline liquid phase contamination content level is considered. The environment temperature effect on the considered method sensitivity is analyzed.
Keywords: фільтрація